Pengaruh Modal Finansial, Modal Manusia serta Teknologi Terhadap Pertumbuhan Inklusif di Indonesia - Azzahra, Nadzvira; Suseno, Deky Aji (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
High economic growth does not always positively correlate with equitable welfare improvement. Inclusive economic development is needed, emphasizing economic growth that not only increases per capita income but also provides broader and more equitable benefits. This study analyzes the influence of financial capital, human capital, and technology on inclusive economic development, with infrastructure as an intervening variable. The research employs a quantitative method across 34 provinces in Indonesia over eight years, from 2016 to 2023. The data utilized in this study consists of secondary data sourced from the Central Statistics Agency (Badan Pusat Statistik or BPS) and the Directorate General of Fiscal Balance (Direktorat Jenderal Perimbangan Keuangan or DJPK). The study is grounded in endogenous economic growth theory, public finance theory, and Amartya Sen's capability approach. Data analysis uses the Partial Least Square (PLS) method with WarpPLS 7.0 software. The results indicate that financial capital contributes positively to inclusive economic development and infrastructure, with coefficient values of 0.63 and 0.52, respectively. Furthermore, human capital and infrastructure also have a significant positive impact on inclusive economic growth, with coefficient values of 0.10 and 0.16, respectively. Meanwhile, technology exhibits a positive but not significant influence on inclusive economic development, with a coefficient value of 0.06.